2016
DOI: 10.3389/fpsyg.2016.01214
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personal and Job Resources in the Relationship between Psychosocial Job Demands, Mental Strain, and Health Problems

Abstract: Recent research highlights the importance of both job resources and personal resources in the job demands-resources model. However, the results of previous studies on how these resources are related to each other and how they operate in relation to the health-impairment process of the job demands-resources model are ambiguous. Thus, the authors tested an alternative model, considering job and personal resources to be domains of the same underlying factor and linking this factor to the health-impairment process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 64 publications
2
28
0
2
Order By: Relevance
“…Again, this effect was relatively weak. Overall, these findings largely conform to previous studies that found both job and personal resources to be important predictors of health and psychological well-being (Kalimo, Pahkin & Mutanen, 2002; Mayerl et al, 2016). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Again, this effect was relatively weak. Overall, these findings largely conform to previous studies that found both job and personal resources to be important predictors of health and psychological well-being (Kalimo, Pahkin & Mutanen, 2002; Mayerl et al, 2016). …”
Section: Discussionsupporting
confidence: 90%
“…In a second step, we estimated a multinomial logistic regression model by having the latent variable for symptom clusters regress on the latent variable for stress profiles. Moreover, given that job resources and self-efficacy were found to show substantial relationships to both work-related stress and health (see e.g., Mayerl et al, 2016; Xanthopoulou et al, 2007), we controlled for their confounding effects by including them as covariates in the final regression model. Additionally, we considered gender, age, education, and occupational groups.…”
Section: Methodsmentioning
confidence: 99%
“…Again, this effect was relatively weak. Overall, these findings largely conform to previous studies that found both job and personal resources to be important predictors of health and psychological well-being (Kalimo et al, 2002;Mayerl et al, 2016).…”
Section: /21supporting
confidence: 90%
“…Moreover, given that job resources and self-efficacy were found to show substantial relationships to both work-related stress and health (see e.g. Mayerl et al, 2016;Xanthopoulou et al, 2007), we controlled for their confounding effects by including them as covariates in the final regression model. Additionally, we considered gender, age, education, and occupational groups.…”
Section: /21mentioning
confidence: 99%
“…Embora os transtornos mentais possuam uma etiologia multicausal em que conjuntos de diversos fatores interagem de modo complexo (Jaques, 2007), pode-se considerar na contribuição dos estressores presentes no atual contexto educacional e organização do trabalho docente devido às categorias de afastamento dos professores investigados. Estudos têm revelado forte associação entre estressores ocupacionais e transtornos mentais em professores (Carlotto & Câmara, 2015;Gasparini et al, 2006;Guglielmi & Tatrow, 1998;Mayerl, Stolz, Waxenegger, Rásky, & Freidl, 2016). O afastamento em professores possui um agravante relacionado às características do seu trabalho, com altas demandas cognitivas, pois segundo Zijlstra et al (2006), quanto maiores as demandas cognitivas antes do absenteísmo, mais difícil o retorno, fazendo com que o trabalhador passe a considerar uma outra opção de trabalho.…”
Section: Discussionunclassified